AI, education and digital sovereignty - Hamadeh, Shereen; Amin, Hira (Frontiers in Education, 2025)
Artificial intelligence (AI) is rapidly being embedded into all aspects of human life, reshaping everything from mundane daily human interactions to national military strategies. With AI technological capabilities limited to only a handful of parties, nations must grapple with the effects of relying on foreign technology on their own digital sovereignty, which is defined as a nation’s ability to control its digital infrastructure, data flows, and epistemic frameworks. This paper traces the recent AI educational policies of China and the United States—the world’s leading economic and technological powers. Analyzing state discourse, policies and governance between 2017 and 2025 this paper argues that the new AI race has revitalized the discourse on digital sovereignty. AI education is now a core feature of national security, workforce competitiveness and cultural sovereignty. This framing elevates AI from a tool of innovation to an instrument of geopolitical power, and places education, skills and capacity building at the heart of this strategic landscape.